Інтернет-торгівля як ключовий інструмент розвитку галузі еко-продукції в Україні - Кітченко, Олена Миколаївна; Костенко, Тетяна Вячеславівна; Пригоров, Сергій Геннадійович (НТУ "ХПІ", 2015)
У статті розглядаються питання пов’язані з перспективами збуту еко-продукції на вітчизняному ринку непродовольчих товарів. Досліджується ефективність інтернет-торгівлі як одного з найперспективніших каналів збуту еко-продукції в Україні. Проводиться стислий огляд інтернет-аудиторії в Україні, а також огляд інтернет-магазинів еко-продукції, надаються їх основні переваги та недоліки. Проводиться аналіз контенту найбільш відвідуваних українських інтернет-магазинів еко-продукції. Надаються аргументи щодо застосування інструментів SEO оптимізації.

The article deals with issues related to the prospects of selling eco-products in the domestic market of consumer goods. The efficiency of e-commerce as one of the most promising channels of eco-products in our country is considered. A study of the largest online retailers for product lines is conducted. It was established that the percentage of shops that are engaged only in the implementation of non-food products increased in recent years. The brief overview of the Internet audience in Ukraine is studied. The main advantages and disadvantages in the online stores are identified. Using of tools SEO and SMM optimization makes it possible to overcome the shortcomings identified is considered. The analysis of domestic biggest online store in order to assess the quality of the content by indicators is held. The arguments on the application of SEO optimization tools are given. The study, makes it possible to conclude that demand for eco-products heterogeneous, concentrated in large cities, but a third of consumers living in medium and small cities and villages. As demand a shared, so the Internet is the most optimal sales channel of eco-products, because it has the widest coverage of consumers.
Internet commerce as a key tool for the development of eco-products industry in Ukraine
Keywords: інтернет-магазин; органічні товари; SEO-оптимізація; канали збуту; online shop; organic products; SEO-optimization; sales channels; Internet trade